Seni Muqabalah dalam Al-Qur'an Surat Al-Mulk : Studi Ilmu Badi’ - Tria Wulandari; Mawaddah Mumtazah; Andini Rahmawati; Harun Al-Rasyid (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This article aims to analyze the use of muqabalah as a language style in Surah Al-Mulk and its impact on conveying moral and spiritual messages in the Al-Qur'an. Using a qualitative approach, this research analyzes verses containing muqabalah and discusses various contrasts that arise, such as life and death, courage and fear, and luck and loss. The methodology used includes literature study, tafsir, and rhetorical analysis to explore how muqabalah enriches the meaning of the text and increases reader understanding. The results of this research show that there is Muqabalah Khilafi in verse 3, Muqabalah Naziri in verse 15, and Muqabalah Naqidhi in verses 20, 21, and 22. These findings confirm that the use of muqabalah in Surah Al-Mulk not only clarifies the meaning, but also has a psychological impact profound for readers. The contrasts displayed serve to increase moral awareness and spiritual responsibility, as well as provide relevance to these messages in modern life. The uniqueness of this research lies in its emphasis on how muqabalah can be applied in learning the Koran in the contemporary era, as well as providing suggestions for increasing spiritual awareness through creative and relevant approaches. Thus, it is hoped that this research can contribute to a better understanding and application of the teachings of the Qur'an among Muslims.